Analisa kerja mesin CNC laser cutting CO2 2 axis berbasis MACH3 pada variasi pemotongan - Giri Halim; Asroni Asroni; Eko Budiyanto (Universitas Muhammadiyah Metro, 2022)
Laser technology is now so rapidly and is used in almost all fields, such as in manufacturing, medical, arts, trade transactions and printing. Although there are various types of lasers on the market, the C02 laser is the most common in manufacturing. This is due to its relatively large power so that its use is more flexible and can be used for cutting thin sheet materials as well as rather thick materials. Laser cutting has various advantages over other manufacturing technologies because it can receive data directly from the computer, so that cutting automation can run in the industrial world. The use of CNC (Computer Numerical Control) machines in laser cutting systems is very necessary, because we can cut a material with the design shape we want and with good cutting quality. The method used is experimental by designing and manufacturing and testing a CO2 laser cutting CNC machine. Testing is done by finding the best feedrate and knowing the level of accuracy of the cutting results on different types of cutting grooves. From the results of the study it can be concluded that the best feedrate is 50 mm/min, and also the level of accuracy with different groove cutting shapes affects the level of cutting accuracy, the lowest accuracy coefficient is 0.73 mm.